Tindak Tutur Ilokusi dalam Video “Mencoba menjadi Tunanetra dalam Sehari” pada Kanal Youtube Froyonion dan Kelayakannya sebagai Bahan Ajar Pembelajaran Teks Tanggapan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Youtube social media is still one of the forms of communication media that is widely used in society, which of course there are many speech acts that follow it. This research is motivated by the relationship between communication in society which is accompanied by the many illocutionary speech acts used by people in videos uploaded on Youtube social media. In addition, this study aims to describe the illocutionary speech acts in the video